Evaluation of the RABBIT Risk Score for serious infections. Issue 9 (5th June 2013) - Zink, A; Manger, B; Kaufmann, J; Eisterhues, C; Krause, A; Listing, J; Strangfeld, A
Abstract : Objective: To evaluate the Rheumatoid Arthritis Observation of Biologic Therapy (RABBIT) Risk Score for serious infections in patients with rheumatoid arthritis (RA). Methods: The RABBIT Risk Score for serious infections was developed in 2011 on a cohort of RA patients enrolled in the German biologics register RABBIT between 2001 and 2007. To evaluate this score, we used data from patients enrolled in RABBIT after 1 January 2009. Expected numbers of serious infections and expected numbers of patients with at least one serious infection per year were calculated by means of the RABBIT Risk Score and compared with observed numbers in the evaluation sample. Results: The evaluation of the score in an independent cohort of 1522 RA patients treated with tumour necrosis factor α (TNFα) inhibitors and 1468 patients treated with non-biological disease-modifying antirheumatic drugs (DMARDs) showed excellent agreement between observed and expected rates of serious infections. For patients exposed to TNF inhibitors, expected as well as observed numbers of serious infections were 3.0 per 100 patient-years (PY). For patients on non-biological DMARDs the expected and observed numbers were 1.5/100 PY and 1.8/100 PY, respectively. The score was highly predictive in groups of patients with low as well as with high infection risk. Conclusions: The RABBIT Risk Score is a reliable instrument which determines the risk of serious infection in individual patients based on clinical and treatment information. It helps the rheumatologist to balance benefits and risks of treatment, to avoid high-risk treatment combinations and thus to make informed clinical decisions.